1983
DOI: 10.1111/j.1600-0609.1983.tb01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Implanted Autologous Splenic Tissue in Splenectomized Rats Exposed to i.v. Streptococcus Pneumoniae

Abstract: The protective effect of splenic implantation or hemisplenectomy on the survival rate was studied in 34 Wistar rats inoculated intravenously with 8.5 × 106 CFU Streptococcus pneumoniae type 25. 4 months prior to the bacterial challenge, different surgical procedures were performed, dividing the animals into 5 equally large groups: (1) sham operation, (2) hemisplenectomy, (3) splenectomy with a 100% reimplantation, (4) splenectomy with a 50% reimplantation, and (5) splenectomy without reimplantation. The observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The capability of regenerated splenic autotransplants of recovering its primary immune function is still controversial. Although many studies reported immunoprotective effects of implanted autologous splenic tissue against infection in rats [7][8][9][10][11] as well as in man [12,13], a few other studies observed no beneficial effects [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The capability of regenerated splenic autotransplants of recovering its primary immune function is still controversial. Although many studies reported immunoprotective effects of implanted autologous splenic tissue against infection in rats [7][8][9][10][11] as well as in man [12,13], a few other studies observed no beneficial effects [14][15][16].…”
Section: Introductionmentioning
confidence: 99%